The impact of the arbitration clause on the rights of partners in partnership companies in light of the personal nature of the company - Al dawoud, Mohammad Mahmoud Said; Al Da'jeh, Asia Khalaf Mohammad; Al-Wreikat, Eman; Alhiniti, Yasar; Qouteshat, Ehab (Research Journal in Advanced Humanities, 2026)
The current investigation aims to explore the duration of partners' commitment to the arbitration clause stipulated in the partnership agreement, whether partners are joining the company or departing, with a focus on the legal consequences of special dissolution that are particular to partnerships. The significance lies in the effect on those who were not involved in the contract, such as heirs. Besides, the paper aims to highlight the extent to which the arbitration clause is effective against third parties who enter into contracts with the company under the existence of such a clause. The study was based on a primary issue, which is the degree to which the arbitration clause is in conflict with the personal nature of partnerships that are formed based on personal sentiment and mutual trust between the partners, as well as the consequences of this conflict in the event of having to implement the arbitration clause on a partner without their consent, and in the event of the emergence of disputes regarding the clause's validity, as well as the state of the legal systems in Jordan regarding these issues. The method of study is analytical and involves deconstructing the foundations of partnerships and clarifying the effects of the inclusion of arbitration clause in them, as well as the legal responsibility associated with their use and the consequences of their infringement. The investigation also employed a comparative approach by reviewing the Jordanian laws in regard to some of the tendencies of the Anglo-Saxon legal systems to be benefitted from their advanced features, in order to highlight areas of discrepancy, divergence and convergences between them. The investigation has yielded some results, the most significant of which is the existence of partial conflict in some instances where the arbitration clause is in conflict with the nature of the partnership, unless the partnership's contract includes an express stipulation regarding the scope of the clause, as well as a legislative deficiency in regulating arbitration in partnerships that takes into account their special attributes. Based on this, the study advocates for the necessity of enacting stringent legislative rules that would regulate the application of arbitration clauses in partnerships and determine their scope and limits.